Analyzing High School Students’ Mulitmodal Compositions with Digital Media Platforms Using Metafunctions - Stewart, Olivia G. (Language and Literacy / Langue et littératie, 2024)
This study explores how diverse high school English students designed open-ended, multimodal projects across digital platforms (Weebly, blogs, and Instagram). Framed by metafunctions, emergent and axial coding of each student’s website homepage shows a broad range of how they designed in digital spaces and to what rhetorical effects. Additional coding of two focal students’ designs across each of the digital platforms highlights how students created complex, multimodal compositions that would have otherwise not been possible with the typical more formal, rigid forms of discourse. By designing multimodally, students showcased interests, humor, emotions, and culture not often seen in this classroom.